Exogenous Fe2+ alleviated the toxicity of CuO nanoparticles on Pseudomonas tolaasii Y-11 under different nitrogen sources - Yuran Yang; Can Zhang; Xuejiao Huang; Xuwei Gui; Yifang Luo; Zhenlun Li (PeerJ, 2020)
Extensive use of CuO nanoparticles (CuO-NPs ) inevitably leads to their accumulation in wastewater and toxicity to microorganisms that effectively treat nitrogen pollution. Due to the effects of different mediums, the sources of CuO-NPs-induced toxicity to microorganisms and methods to mitigating the toxicity are still unclear. In this study, CuO-NPs were found to impact the nitrate reduction of Pseudomonas tolaasii Y-11 mainly through the action of NPs themselves while inhibiting the ammonium transformation of strain Y-11 through releasing Cu2+. As the content of CuO-NPs increased from 0 to 20 mg/L, the removal efficiency of NO3− and NH4+ decreased from 42.29% and 29.83% to 2.05% and 2.33%, respectively. Exogenous Fe2+ significantly promoted the aggregation of CuO-NPs, reduced the possibility of contact with bacteria, and slowed down the damage of CuO-NPs to strain Y-11. When 0.01 mol/L Fe2+ was added to 0, 1, 5, 10 and 20 mg/L CuO-NPs treatment, the removal efficiencies of NO3- were 69.77%, 88.93%, 80.51%, 36.17% and 2.47%, respectively; the removal efficiencies of NH4+ were 55.95%, 96.71%, 38.11%, 20.71% and 7.43%, respectively. This study provides a method for mitigating the toxicity of CuO-NPs on functional microorganisms.